A review of intensive mode of delivery and science subjects in Australian universities. Issue 3 (3rd July 2017) - Harvey, Marina; Power, Michelle; Wilson, Michael
Abstract: One response to the global trend of increasing rates of student participation in tertiary education has been for universities to increase the number of intensive mode of delivery subjects available. This phenomenon extends to science subjects. Embarking on offering an undergraduate science subject in intensive mode for the first time at the Australian case example university, it was essential to first learn about good pedagogical design and practice from other educational organisations. To achieve this, a website audit of Australian universities was undertaken in tandem with a critical review of the Australian and international literature on intensive mode of delivery. While it was found that a majority of Australian universities offer science subjects in intensive mode, these subjects were primarily at the postgraduate level of study. The literature focusing on intensive mode in science was minimal. It revealed definitional ambiguity and conceptual non-uniformity as well as a range of positive, negative and inconclusive results in relation to the academic and 'real-world' outcomes of intensive mode. This review identifies a need for evidenced-based empirical research into the pedagogy around intensive mode for undergraduate science subjects.